2006
DOI: 10.5194/bg-3-1-2006
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms and their influence on the biologically mediated uptake of atmospheric CO<sub>2</sub> in the Arabian Sea upwelling system

Abstract: Abstract. Sediment trap experiments have been carried out in order to study processes controlling shifts from diatom to non-diatom dominated systems in the western Arabian Sea. One of our major problems was to link sediment trap records to surface ocean processes. Satellite-derived observations on upper ocean parameters were helpful to reduce this problem in the past and gain a new quality by combining it with results obtained during the Joint Global Ocean Flux Study (JGOFS) in the Arabian Sea. The new results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 72 publications
(79 reference statements)
3
11
0
Order By: Relevance
“…In freshwater environments, chytrid infections modify phytoplankton composition (Holfeld, ; Ibelings et al ., ; Kagami et al ., ), impacting bloom progression and primary productivity (Gleason et al ., ; Rasconi et al ., ). In upwelling ecosystems, the decline of diatom blooms has been mainly attributed to depletion of nutrients (Barlow, ) and grazing (Rixen et al ., ). We challenge these views and propose that parasitic Fungi are partly responsible for falling marine diatom populations.…”
Section: Resultsmentioning
confidence: 97%
“…In freshwater environments, chytrid infections modify phytoplankton composition (Holfeld, ; Ibelings et al ., ; Kagami et al ., ), impacting bloom progression and primary productivity (Gleason et al ., ; Rasconi et al ., ). In upwelling ecosystems, the decline of diatom blooms has been mainly attributed to depletion of nutrients (Barlow, ) and grazing (Rixen et al ., ). We challenge these views and propose that parasitic Fungi are partly responsible for falling marine diatom populations.…”
Section: Resultsmentioning
confidence: 97%
“…Based on the growing evidence that low concentrations of dissolved oxygen slow down the respiration of organic matter in the water column and thereby the biological oxygen consumption (Aumont et al, 2015;Cavan et al, 2017;Laufkötter et al, 2017;Thamdrup et al, 2012;Van Mooy et al, 2002), it has been hypothesized that an oxygen-related feedback mechanism stabilizes the Arabian Sea OMZ (Rixen et al, 2019a). This mechanism operates in the upper part of the OMZ, which hosts the seasonal thermocline but also affects the base of the OMZ and thereby its thickness as discussed before (Fig.…”
Section: Biological Feedback Mechanismmentioning
confidence: 96%
“…3c, Antoine et al, 1996;Naqvi, 1991). The offshore advection of upwelling-driven blooms, which increases the organic carbon export into the central Arabian Sea (Rixen et al, 2006), contributes to this eastward displacement of the OMZ, but monsoon-driven and seasonally varying physical oxygen supply mechanisms are assumed to be the main processes causing it. Numerical model studies have shown that, on an annual timescale, mesoscale eddies and filaments dominate the vertical supply of oxygen to the OMZ and the lateral transport of ventilated waters into the central and northern Arabian Sea (Resplandy et al, 2011(Resplandy et al, , 2012.…”
Section: Spatial and Temporal Variability Of The Arabian Sea Omzmentioning
confidence: 99%
See 1 more Smart Citation
“…The low areal extension appears to be a consequence of the inflow of ICW because it favors the eastward retreat of the OMZ in the western Arabian Sea while it attenuates the influence of the clockwise circulation and the associated southwards expansion of the OMZ in the eastern Arabian Sea. The summer-monsoon-driven upwelling and the resulting offshore advection of blooms along filaments increase the carbon export in the central Arabian Sea (Rixen et al, 2006a) which in turn explains the low oxygen concentrations during the summer monsoon.…”
Section: Omz and Upwellingmentioning
confidence: 99%